Pola Konsumsi Ikan Di Kalangan Masyarakat Perkotaan Dan Implikasinya Terhadap Kebijakan Pangan Nasional - Sinaga, Herianti (Jurnal Perikanan dan Kelautan, 2025)
This study aims to analyze fish consumption patterns among urban communities in Indonesia and their implications for national food policy. Using a survey method involving 400 respondents across four major cities, supported by in-depth interviews, the study finds that fish consumption in urban areas remains relatively low. Key influencing factors include limited access to fresh fish, fluctuating prices, and a preference for convenient foods. The most commonly consumed fish are freshwater species such as catfish and tilapia, while nutrient-rich marine fish are more commonly consumed by higher-income groups. The analysis also reveals a significant correlation between education level, income, and the frequency of fish consumption. These findings indicate the need for policies that promote fish consumption through nutrition education, strengthened food distribution systems, and innovation in affordable and practical processed fish products. Increasing fish consumption in urban areas holds substantial potential to support food security and improve community nutrition in a sustainable manner.